تطور شركات الأعمال العائلية في ولاية سوق أهراس - دراسة ميدانية شركة الاعمال العائلية الاخوة زاوي - - صالح الدين كواشي; محمد أمين زاوي (My University, 2021)
This study attempts to shed light on the development of family business companies, and to achieve this aim, the topic shall be tackled from both a theoretical and practical perspectives. The first part discusses various assumptions concerning family business companies in its conceptual frame as well as its development. Moreover, the practical side emphasizes that the development of family business companies goes through phases which include: the founder, the siblings and the extended family. It is equally important to focus on a series of important factors that can assist this companies to achieve their success and guarantee their continuity even in its darkest times. .................................... تحاول هذه الدراسة تسليط الضوء على تطور الشركات العائلية، ولتحقيق هذا الهدف يجب تناول الموضوع من الناحيتين النظرية والعملية. يناقش الجزء الأول الافتراضات المختلفة المتعلقة بالشركات العائلية في إطارها المفاهيمي وتطورها. علاوة على ذلك، يؤكد الجانب العملي على أن تطور الشركات العائلية يمر بمراحل تشمل: المؤسس، والأشقاء، والعائلة الممتدة. ومن المهم بنفس القدر التركيز على سلسلة من العوامل المهمة التي يمكن أن تساعد هذه الشركات على تحقيق نجاحها وضمان استمراريتها حتى في أحلك الأوقات.